Das Leben bejahen: Jesu Tod, ein Opfer: zur Bedeutung der unterscheidenden Rede von "victima" und "oblatio" - Kreinecker, Christina M. (Zeitschrift für katholische Theologie, 2006)
The interpretation of Jesus' death as a sacrifice produces a lot of misunderstandings. In this paper the concepts of victima and oblatio are linguistically, critically and systematically analyzed according to their content. As its main thesis the paper emphasizes the necessary distinction between victima and oblatio and claims that in theological terms Jesus' death can only be understood as an oblatio and not as a sacrificium. Oblatio belongs to the category „life" and includes aspects like atonement/expiation, substitution and offering.